Cutting device for preparing carbon fiber filter plate - GUO XIAODONG; KONG LINGQIANG; SONG JIEBIN; JIAO LEI; GUO JIANDONG; SUN QIFEI; JI ZHENGLEI (2023)
The invention relates to the technical field of carbon fiber filter plate cutting equipment, in particular to a cutting device for carbon fiber filter plate preparation, which comprises a positioning assembly, a cutting assembly, a transfer assembly and a fixing assembly, the cutting assembly is mounted at the bottom of the positioning assembly, and the transfer assembly and the fixing assembly are both located in the positioning assembly. And the transfer assembly is mounted above one side of the positioning assembly. The cutting device has the beneficial effects that when the cutting device works, the cutting disc extends out to facilitate cutting of a hardness plate, the cutting position of the hardness plate is pressed by matching with the protection plate, the situation that the hardness plate is tilted during cutting is avoided, the cutting device can conveniently cut the hardness plate, the cutting efficiency of the cutting device is higher, and when the cutting disc is idle, the cutting disc is not da